1998
DOI: 10.1016/s0896-6273(00)81013-2
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory Reciprocal Synapses: Dendritic Signaling in the CNS

Abstract: Synaptic transmission between dendrites in the olfactory bulb is thought to play a major role in the processing of olfactory information. Glutamate released from mitral cell dendrites excites the dendrites of granule cells, which in turn mediate GABAergic dendrodendritic inhibition back onto mitral dendrites. We examined the mechanisms governing reciprocal dendritic transmission in rat olfactory bulb slices. We find that NMDA receptors play a critical role in this dendrodendritic inhibition. As with axonic syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

45
565
5

Year Published

1999
1999
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 468 publications
(615 citation statements)
references
References 48 publications
45
565
5
Order By: Relevance
“…It has been shown that dendrodendritic synapses possess unique functional properties, such as a dependence on NMDA receptors rather than AMPA receptors for their activation (Isaacson and Strowbridge, 1998;Schoppa et al, 1998). Here, we have shown that NMDA and AMPA receptors are colocalized at dendrodendritic synapses and that they are distributed along the entire postsynaptic specialization of granule cell spines.…”
Section: Glutamate Receptors In Granule Cellsmentioning
confidence: 59%
See 2 more Smart Citations
“…It has been shown that dendrodendritic synapses possess unique functional properties, such as a dependence on NMDA receptors rather than AMPA receptors for their activation (Isaacson and Strowbridge, 1998;Schoppa et al, 1998). Here, we have shown that NMDA and AMPA receptors are colocalized at dendrodendritic synapses and that they are distributed along the entire postsynaptic specialization of granule cell spines.…”
Section: Glutamate Receptors In Granule Cellsmentioning
confidence: 59%
“…These studies have demonstrated that mitral cells release glutamate and excite granule cell dendrites (Trombley and Shepherd, 1992;Wellis and Kauer, 1994), which in turn mediate GABAergic inhibition back onto the mitral cells (Nicoll, 1971;Nowycky et al, 1981a;Jahr and Nicoll, 1982;Wellis and Kauer, 1993). Recent electrophysiological investigations have revealed unexpected properties of dendrodendritic synapses, including a dependence on NMDA, rather than AMPA, receptors for the activation of granule cells (Isaacson and Strowbridge, 1998;Schoppa et al, 1998) and a self-excitation of mitral cell dendrites, similarly dependent on NMDA receptors (Aroniadou-Anderjaska et al, 1999;Isaacson, 1999). Based on these observations, one would hypothesize that NMDA receptors are located presynaptically as well as postsynaptically at dendrodendritic synapses, but this remains to be shown by anatomical techniques.…”
Section: Abstract: Dendrodendritic Synapse; Olfactory Bulb; Nmda Recmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar type of neural organization (combination of reciprocal, afferent, and``efferent'' terminals formed by the same``interneuron'' on different cellsÐreciprocal interaction) is very common at the level of second-order neurons in the olfactory bulb and retina. These interneurons have been suspected of forming``reciprocal inhibition circuits '' (Anton et al 1993;Chen et al 2000;Kirillova and Lin 1998;Nakanishi 1995;Woolf et al 1991;Isaacson and Strowbridge 1998).…”
Section: Reciprocal Innervationmentioning
confidence: 99%
“…This type of synaptic relationship has been described in both the central and peripheral nervous systems. Reciprocal synapses are common in the brain (Famiglietti 1970;Guan et al 1995;Marcos et al 1996), retina (Harveit 1999;Dowling 1968), olfactory bulb (Kirillova and Lin 1998;Isaacson and Strowbridge 1998), autonomic nervous system (Kawai 1996;Yagamuchi et al 1975), carotid bulb (McDonald and Mitchell 1975;Matsumoto et al 1980), and vestibular macula (Ross 1997;Dunn 1980;Lysakowski and Goldberg 1997). In the organ of Corti, reciprocal synapses are characterized by the presence of both afferent and efferent types of synaptic membrane specializations between a single nerve ®ber and a hair cell (Nadol 1981).…”
Section: Introductionmentioning
confidence: 99%